Learning the languages of technology: Multilingualism in Indonesian vocational secondary education - Kristian Tamtomo (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
In Indonesia, we can consider vocational secondary education as being in the front lines of global contact, in which youth as students directly face the demands of globalized industries and labor markets. Within vocational high schools, the use of multiple languages often plays an important yet unrecognized part of vocational training. This paper will discuss, based on ethnographic data collected in 2013 from two vocational schools in Semarang, the way in which students use multiple languages, mainly English, Indonesian, and Javanese, as part of their process of learning vocational skills. The main argument of the paper is that vocational schools teach students a specific technical variety or register of language, which combines parts or sometimes fragments of multiple languages, often for the purpose of technical vocational competence and not necessarily for the development of linguistic competence. This results in a form of “segmented competence” (Blommaert and Omoniyi 2006). However, youth as students can use this technical register to not only localize global forms of technological practice in their learning processes but also to participate, albeit marginally, in the global or transnational technology-based communities of practice of their vocational program.Keywords: multilingualism; globalization; youth; vocational high school